2013
DOI: 10.1063/1.4802006
|View full text |Cite
|
Sign up to set email alerts
|

Relation between occupation in the first coordination shells and Widom line in core-softened potentials

Abstract: Three core-softened families of potentials are checked for the presence of density and diffusion anomalies. These potentials exhibit a repulsive core with a softening region and at larger distances an attractive well. We found that the region in the pressure-temperature phase diagram in which the anomalies are present increases if the slope between the core-softened scale and the attractive part of the potential decreases. The anomalous region also increases if the range of the coresoftened or of the attractiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In fact, for ethanol the TMD line vanishes at χ alc = 0.10, while for 1-propanol the TMD is only observed at χ alc = 0.01the TMD lines are shown in the figure 4(a). The water anomalous behavior is related to the competition between two liquids that coexist [14,88,89]. This competition can be observed using the g ww (r).…”
Section: B Water-short Alcohol Mixturesmentioning
confidence: 99%
“…In fact, for ethanol the TMD line vanishes at χ alc = 0.10, while for 1-propanol the TMD is only observed at χ alc = 0.01the TMD lines are shown in the figure 4(a). The water anomalous behavior is related to the competition between two liquids that coexist [14,88,89]. This competition can be observed using the g ww (r).…”
Section: B Water-short Alcohol Mixturesmentioning
confidence: 99%
“…[39][40][41][42][43][44]. The FSC of the structural α-relaxation in water has been related to the crossing of a liquid-liquid Widom line [45][46][47][48][49][50][51][52][53] (WL), the line of collapse of the maxima in response functions that converge to a liquid-liquid critical point (LLCP). 39,40,54 Therefore the FSC that we found could be the trace of the presence of a WL and consequently of a LLCP in the phase diagram of protein hydration water.…”
Section: The α-Relaxation and The Fragile-to-strong Transitionmentioning
confidence: 99%
“…Widom line associated with the presence of a possible liquidliquid critical point. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the region of the gas-liquid transition, it is generally observed that departing from the critical point and entering into the supercritical region the maxima of the response functions progressively weaken. The range of definition of the Widom line is particularly relevant for water since it is equivalent to the range where the peculiar properties of supercritical water are evidenced.…”
Section: Introductionmentioning
confidence: 99%